The Arabic Version of Aristotle's Historia Animalium, Book I-X of Kitāb al-Hayawān. - L.S. Filius (Aristoteles Semitico-Latinus, 2018)
Aristotle's Historia Animalium is one of the most famous and influential zoological works that was ever written. It was translated into Arabic in the 9th century CE together with Aristotle's other zoological works, On the Generation of Animals and On the Parts of Animals . As a result, the influence of Aristotelian zoology is widely traceable in classical Arabic literary culture and thought. The Arabic translation found its way into Europe through the 13th-century Latin translation by Michael Scotus, which was extensively used by medieval European scholars. A critical edition of the Arabic Historia Animalium has long been awaited, and Lourus Filius's edition, based on all extant Arabic MSS, as well as on Scotus's Latin translation, can rightly be seen as a scholarly landmark.